Določitev malociklične nosilnosti kotalnega stika - Kunc, Robert (Kovine zlitine tehnologije, 1999)
The carrying capacity of large axial bearings with surface hardened raceway is usually given with the maximal permissible force on the rolling element with the highest load. The established criteria of the maximal premissible plastic deformation of the raceway, and the maximal allowed subsurface stress on the hardened layer boundary give widely varying values for the carrying capacity of the rolling contacts. On the models of bearing raceways from 42CrMo4 and C45 steels we have determined the cyclic curves (force - deformation), the limit of fast increase in (elastic and plastic) deformation gradient, and the size of the contact surface. The sub surface stresses were simultaneously checked using a FEM model and considering the material nonlinearities.
Keywords: aksialni ležaji; obremenitve; nosilnost